Black Empowerment and White Mobilization: The Effects of the Voting Rights Act - Andrea Bernini; Giovanni Facchini; Marco Tabellini; Cecilia Testa (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2023)
The 1965 Voting Rights Act (VRA) paved the road to Black empowerment. How did southern whites respond? Leveraging newly digitized data on county-level voter registration rates by race between 1956 and 1980, and exploiting pre-determined variation in exposure to the federal intervention, we document that the VRA increases both Black and white political participation. Consistent with the VRA triggering countermobilization, the surge in white registrations is concentrated where Black political empowerment is more tangible and salient due to the election of African Americans in county commissions. Additional analysis suggests that the VRA has long-lasting negative effects on whites' racial attitudes.
Keywords: D72; J15; H70; N92; 330; Civil Rights; Race; Voting Behavior; Enfranchisement